Aerodynamic Performance Prediction of XH-59A Helicopter in Pop-up Flight. Issue 1 (September 2020) - You, K; Zhao, X; Zhang, Y-H; Zhao, S-Z; Lin, Y-F
Abstract: The pop-up progress of the coaxial rigid rotor helicopter was decomposed into 5 stages. Quasi-steady flow assumption was adopted to analyze the helicopter performance. XH-59A helicopter was regarded as a solid body. Flow interactions between fuselage and rotor, rotor and tail were ignored. The aerodynamic performance of coaxial rotor, fuselage and horizontal tail were calculated based on Blade element moment theory, wind tunnel test data and theoretical calculation correspondingly. The Pitt/Peters inflow model was used to represent the inflow velocity on the rotor and flow interaction between upper and lower rotor were considered using interference factor. The net force and moment on the helicopter was derived and formulated into flight mechanics equations. To validate the calculation, a wind tunnel test of a coaxial rigid rotor helicopter was employed. The rotor lift coefficient, helicopter pitching and rolling moment coefficients were close to the experimental data. The controlled variables of the helicopter was composed of helicopter pitch angle (shaft angle), collective pitch, cyclic pitch of both rotors, deflection angle of the horizontal tail during the pop-up progress. The mathematical model presented in this paper provides the basic system structure to analyze the pop-up progress. The required power of the helicopter were formulated with altitude, rotor thrust, flight velocity, which help to obtain a rapid and primary evaluation of the integral performance of the progress.